ANALISIS PENGARUH MANAJEMEN LABA TERHADAP TINGKAT PENGUNGKAPAN LAPORAN KEUANGAN - Purba, Riky Kristy (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
The purpose of this research is to find out the correlation which occurs between earnings management which is measured by using short-term discretionary accruals and long-term discretionary accruals with financial statement disclosure with financial statement disclosure level at manufacturing companies which are listed in Indonesia Stock Exchange in 2010-2012. This research is based on the comprehension that among these two variables can influence one to another. The data analysis technique is simultaneous equation model by using two-stage least square test method and purposive sampling method is used in determining sample. The result of the research shows that there is simultaneous influence between earnings management through long-term discretionary accruals and financial statement disclosure level. Whereas the earnings management through short-term discretionary accruals has not been proven have simultaneous correlation with the financial statement disclosure level. This research also uses some exogenous variables which have an influence to the earnings management and disclosure level that is companyâs size, profitability, leverage, and liquidity. The result of t-test shows that leverage variable has no influence to the earnings management through long-term discretionary accruals whereas the financial statement disclosure index only profitability variable that has no influence to the financial statement disclosure index.Keywords: Long-term Discretionary Accruals, Financial Statement Disclosure Level, Simultaneous